Tissue Detection and Typisation of Human Papillomavirus in Women with Squamous Intraepithelial Lesions and Squamous Invasive Carcinoma of the Cervix - Dabeski, Drage; Danilovski, Dragan; Antovska, Vesna; Basheska, Neli; Popovska, Zora; Avramovska, Maja (Македонско лекарско друштво = Macedonian medical association, 2015)
Introduction. The most common risk factor for intraepithelial lesions and cervical carcinoma is infection with human papillomavirus (HPV), especially with high-risk HPV genotypes. Only persistent, high-risk HPV infections represent a major risk factor for intraepithelial lesions and cervical cancer. The aims of the study were: detection and typisation of HPV genotypes, which are the most common causes of intraepithelial lesions and cervical cancer, determination of the correlation between HPV infection and histopathological diagnosis, and the correlation between the grade of lesion of the cervix and oncogenic potential of the virus as well as determination of the most affected age group of patients. Methods. This cross-sectional study included 100 sexually active patients with an abnormal Pap test at the age from 20 to 69 years (39±10.77), and was conducted at the University Clinic of Gynecology and Obstetrics in Skopje and University Clinic of Radiotherapy and Oncology in Skopje in the period from January 2014 to August 2014. In all patients colposcopic cervical biopsy was made with endocervical curettage for histopathological analysis and cervical biopsy for detection and HPV typisation. HPV detection and typisation were done using polymerase chain reaction (PCR) and reverse hybridization. Results. HPV DNA was detected in 81.0% (81/100) of the examined women. The relationship between the prevalence of high-risk and low-risk HPV DNA genotypes was 72.0%:9.0%. The frequency of high-risk HPV DNA genotypes ranged from: 54.5% (12/22) in productive HPV infection-mild dysplasia, 86.4% (19/22) with moderate dysplasia, 91.2% (21/23) in severe dysplasia to 100% of squamous cell carcinoma in situ (6/6) and invasive squamous cell carcinoma (5/5). Mixed HPV infection was detected in 19.0% (19/100) of all patients, in 23.5% (19/81) of HPV DNA positive patients. The most common HPV DNA genotypes, in descending order, were HPV 16 (43.2%), HPV 31 (28.4%), HPV 18 (14.8%), etc. The highest frequency of HPV infection was found in patients under 30 years of age. Conclusion. There was an association between HPV infection and squamous intraepithelial lesions and squamous invasive carcinoma of the cervix. There was a correlation between the grade of cervical lesion and the oncogenic potential of the virus. The results of this study may be useful for building a national strategy in the fight against cervical cancer.
Tкивна детекција и типизација на хуман папилома вирусот кај жени со сквамозни интраепителни лезии и сквамозен инвазивен карцином на грлото на матката
Keywords: intraepithelial lesions; human papilloma virus (HPV); HPV typisation; polymerase chain reaction (PCR); reverse hybridization